The Validity of Pre-Service Teachers’ WASSCE Results in Predicting Academic Performance at the Presbyterian College of Education - William Agyei Brantuo; Vivian Maanu; Theophilus Klu kwasi; Seth Amoako Atta (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
In line with international best practices, countries across the globe are intensifying their teacher education institutions to train world-class teachers to feed their schools. Against this background, this research work tried to determine how robust the admission process at the Presbyterian College of Education, Akropong, is. This is because admitting students into the College of Education is the first step in ensuring a sound teacher training program. The study was quantitative and used secondary data; that is, students' West Africa Senior High School Certificate Examination (WASSCE) entry results against their Final GPA at the College of Education were used for the data analysis. The analysis proved that those who entered the College of Education with good grades from the Senior High School exited with good GPAs, and the inverse was true. The researcher recommends that the college move beyond the regular training and put in measures to ensure that most students can improve their performance to be at par with the current demands of a world-class teacher.